Community Environmental Management: Challenges and Opportunities for a Rural Community of Acapulco, Mexico - Cardona Castaño, Juan Camilo (2025)
Community-based environmental management (CBEM) is an effective tool for addressing environmental issues with the participation of local communities. The objective of this study was to explore the implementation of a CBEM program to address socio-environmental problems, as well as its challenges and opportunities, as perceived from local knowledge—in this case, that of the rural community of El Arenal in Acapulco, Mexico. Field immersion and exploration were used to strengthen CBEM. Additionally, a series of participatory workshops were held with the community to identify socio-environmental issues. Based on the collected information, a SWOT analysis was conducted to identify scenarios of challenges and opportunities. Strategic management (SM) tools were used to perform this analysis. The results showed a preoperational scope, and the strengths, opportunities, weaknesses, and threats indicated that internal conditions are favorable, but external ones are not, as they depend on institutions. In conclusion, the participatory construction of a CBEM program would lead to an improvement in the relationship between the El Arenal community and the Tres Palos lagoon. It would also serve to empower the community in aspects such as control, surveillance, use, utilization, and management of natural resources.